Accuracy of dopaminergic imaging as a biomarker for mild cognitive impairment with Lewy bodies. (May 2021) - Roberts, Gemma; Donaghy, Paul C.; Lloyd, Jim; Durcan, Rory; Petrides, George; Colloby, Sean J.; Lawley, Sarah; Ciafone, Joanna; Hamilton, Calum A.; Firbank, Michael; Allan, Louise; Barnett, Nicola; et al.
Abstract : Background: Dopaminergic imaging is an established biomarker for dementia with Lewy bodies, but its diagnostic accuracy at the mild cognitive impairment (MCI) stage remains uncertain. Aims: To provide robust prospective evidence of the diagnostic accuracy of dopaminergic imaging at the MCI stage to either support or refute its inclusion as a biomarker for the diagnosis of MCI with Lewy bodies. Method: We conducted a prospective diagnostic accuracy study of baseline dopaminergic imaging with [ 123 I] N -ω-fluoropropyl-2β-carbomethoxy-3β-(4-iodophenyl)nortropane single-photon emission computerised tomography ( 123 I-FP-CIT SPECT) in 144 patients with MCI. Images were rated as normal or abnormal by a panel of experts with access to striatal binding ratio results. Follow-up consensus diagnosis based on the presence of core features of Lewy body disease was used as the reference standard. Results: At latest assessment (mean 2 years) 61 patients had probable MCI with Lewy bodies, 26 possible MCI with Lewy bodies and 57 MCI due to Alzheimer's disease. The sensitivity of baseline FP-CIT visual rating for probable MCI with Lewy bodies was 66% (95% CI 52–77%), specificity 88% (76–95%) and accuracy 76% (68–84%), with positive likelihood ratio 5.3. Conclusions: It is over five times as likely for an abnormal scan to be found in probable MCI with Lewy bodies than MCI due to Alzheimer's disease. Dopaminergic imaging appears to be useful at the MCI stage in cases where Lewy body disease is suspected clinically.